PROBLEMS OF THE ECOLOGICAL SECURITY SYSTEM - Kh. Nazarov (Journals Park Publishing, 2024)
In the article, the concept of ecological safety, its significance, its characteristics, objects, the basic content and essence of the concept of ecological safety system, which ensures the minimum level of negative ecologically dangerous effects on human life and health, are disclosed. The stages of implementation of the concept, the directions of the specified activities, the role and importance of these activities for the life of the population and the economy of our republic are shown. In the implementation of the concept, international experiences, especially scientifically-based recommendations are given. In the article, special attention is paid to the measures implemented to ensure environmental safety in Uzbekistan, the importance of ensuring environmental safety in socio-economic development, especially to the rational use of natural resources, especially water resources, its protection and environmental safety, and the use of scientific achievements in this regard. based opinions are expressed.
Keywords: Environmental security, Water and land problems, environmental laws, regulations, standards, biological diversity, environmental degradation, deficiencies in the state management system, resource management.